Guided imagery therapy for reducing hypertension in adolescents - Setiawan, Rosieta Anindya; Priyo, Priyo; Priyanto, Sigit (Innovation in Health for Society, 2024)
Hypertension care in nursing involves a comprehensive approach to managing and reducing high blood pressure in patients. Guided imagery is an effective complementary therapy in hypertension care. However, studies exploring the benefits of this therapy for patients living with hypertension are limited. This study aims to evaluate the effectiveness of guided imagery in reducing hypertension. Using a descriptive case study approach, the study focused on a hypertensive female adolescent. Factors such as obesity, family history of hypertension, high salt consumption, and limited knowledge were identified as contributors to hypertension in adolescents. Non-pharmacological therapies like guided imagery can be used alongside pharmacological treatments to manage hypertension in this population. Community nurses are encouraged to incorporate guided imagery therapy to alleviate symptoms of hypertension and enhance overall patient care. Keywords: Hypertension; community nursing; guided imagery; non-pharmacological therapy; adults nursing